The effect of nanocrystalline cellulose on flow properties of fiber crop aqueous suspension. (15th March 2018) - Gharehkhani, Samira; Seyed Shirazi, Seyed Farid; Yarmand, Hooman; Montazer, Elham; Kazi, Salim Newaz; Ibrahim, Rushdan; Ashjaei, Mehdi; Zulkifli, Nurin Wahidah Binti Mohd; Rahmati, Sadegh
Highlights: The potential of Nanocrystalline cellulose (NCC) to utilize in pulp flow. Rheological and pressure drop characteristic of pulp fiber containing NCC. Drag reduction enhancement due to the presence of 150 ppm NCC in pulp suspension. Abstract: Nanocrystalline cellulose (NCC) a nature-based material, has gained significant attentions for its unique properties. The present study aims to investigate the flow behavior of cellulosic suspension containing non-wood pulp fibers and NCC, by means of rheological and pressure drop measurements. The NCC sample was prepared by sulfuric acid hydrolysis from Acacia mangium fibers. The rheological properties of kenaf/NCC suspensions were studied using viscosity and yield stress measurements. The pressure drop properties of the suspension flow were studied with respect to variation in flow velocity (0.4 m/s–3.6 m/s) and the NCC concentration (70 mg/l and 150 mg/l). The pressure drop results showed that the pulp suspension containing 150 mg/l NCC had higher drag reduction than kenaf suspension alone. The present insights into the flow of pulp/NCC suspension provide a new data and promote the application of NCC in industries.